Association between myeloperoxidase gene polymorphism and familial mediterranean fever in Turkish Children - DEMIR, Aysegul Dogan; GOKNAR, Nilufer; OKTEM, Faruk; Ergen, Hayriye Arzu; Dogan, Akif Nuri; Uzuner, SELÇUK; UZUNER, SELÇUK; Vehapoglu, Aysel; VEHAPOĞLU TÜRKMEN, AYSEL; Yazici, MEBRURE; YAZICI, MEBRURE (My University, 2016)
Background: Familial Mediterranean Fever (FMF) is the most common autoinflammatory disease. Autoinflammatory disorders are characterized by exaggerated immune system responses. Neutrophils and their byproduct, myeloperoxidase, are important components of the innate immune system. In the present study, we searched for myeloperoxidase gene polymorphisms in FMF patients. Methodology/Principal Findings: We evaluated 83 children diagnosed with FMF by their physicians and 93 controls without any family history of FMF. MPO gene polymorphisms were detected using polymerase chain reaction (PCR)-based methods. We genotyped all samples in terms of the -463G/A single-nucleotide polymorphism, the most extensively studied MPO polymorphism. Allelic and genotypic frequencies were calculated, and possible associations with FMF explored. The frequencies of MPO polymorphisms differed significantly between the study and control groups (P = 0.003). The AA and AG gene polymorphisms were more prevalent in the FMF group than in the controls. The A allele was more prevalent in the FMF group (P = 0.001), and the frequency of the G allele was similar between the two groups (P = 0.128). Conclusion: MPO gene polymorphisms and allelic differences may be important in the pathogenesis of FMF.